Produksi Enzim Protease Aspergillus Flavus Pam-25 Dengan Variasi Ph Dan Waktu Inkubasi - Indra Prawira; MG. Isworo Rukmi; w wijanarka (Jurnal Akademika Biologi, 2015)
Enzyme is a biokatalisator which can increase the speed of the reaction without join react. Protease enzyme is one of the enzymes that have a high economic value because its application is extensive in the field of industry. Protease is an enzyme that catalyzes the proteolytic peptide bonds in proteins termination. This research aims to determine the effect of pH and incubation time on the production of protease enzyme from A. flavus PaM-25.. This research aims to know the influence of the variation of the pH of the incubation time and against the production of the enzyme protease of A. flavus PaM-25. The research  was conducted at the laboratories of Microbiology Department of Biology, Faculty of Science and Mathematics, University of Diponegoro. Variables observed were protease activity, protein content and specific activity. Research using randomized complete block design (RAK) with two factors. The first factor is variation of pH, P1 (pH 7), P2 (pH 8), and P3 (pH 9), while the second factor is the incubation time T5 (5th day), T6 (6th day) and T7 (7th day) with repeated 3 times. Research data analyzed by Analysis of variance (ANOVA) and continued by Least Significant Difference test and Duncan Significant Difference Test at test level 5%. The results showed that the Aspergillus flavus PaM-25 has the capability of producing alkaline protease enzymes with pH range 7.0-9.0. The highest activity of proteases of   A. flavus PaM-25 retrieved on 7th day incubation time of treatment with protease activity value 1.94 U/mL, while pH treatment has no effect. The highest levels of protein found in the treatment of pH 7 and 5th days of incubation time of 1.05 mg/mL. The value of the highest purity of enzymes found in the combination of treatment pH 9 and 7th day incubation time  of 12.91 U/mg protein